Positive pole piece of lithium iron phosphate battery, preparation method of positive pole piece and lithium ion battery

By adopting double-layer coating technology in the positive electrode sheet of lithium iron phosphate battery, combining lithium iron phosphate material with good conductivity and single-wall carbon nanotubes, the problem of high resistivity caused by thick coating of positive electrode sheet is solved, the chemical performance and energy density of the battery is improved, and the battery cell cost is reduced.

CN119560505APending Publication Date: 2025-03-04湖南领湃新能源研究院有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411665226.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The thick coating of the positive electrode of lithium iron phosphate battery leads to a large internal resistance of the battery cell, affecting the electrochemical performance of the battery, especially when charging and discharging is high.

Method used

Using the double-layer coating technology, the first positive electrode coating consists of lithium iron phosphate material, conductive agent and binder, while the second positive electrode coating introduces ternary lithium material and single-wall carbon nanotubes with good conductivity to improve the conductivity of the system and reduce the resistivity of the electrode sheet.

Benefits of technology

Through the double-layer coating technology, the resistivity of the positive electrode sheet is significantly reduced, the chemical performance and energy density of the battery are improved, and the cost of the battery is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560505A_ABST
    Figure CN119560505A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a lithium iron phosphate battery positive pole piece, a preparation method and a lithium ion battery. The positive pole piece of the lithium iron phosphate battery comprises a foil layer, the positive electrode coatings are coated on the front and back surfaces of the foil layer, and comprise a first positive electrode coating close to the foil layer and a second positive electrode coating far away from the foil layer; wherein the first positive electrode coating comprises a first positive electrode active material, a first conductive agent and a first binder, and the first positive electrode active material is a lithium iron phosphate material; the second positive electrode coating comprises a second positive electrode active material, a second conductive agent and a second binder, and the second positive electrode active material comprises a lithium iron phosphate material and a ternary lithium material. Through a double-layer coating technology, a ternary material with good conductivity is introduced as an outer layer, so that the conductivity of an outer layer system is improved, the resistivity of the pole piece is reduced, and the problems of large internal resistance and poor dynamic performance of a positive electrode thick coating are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery positive electrode active materials, and in particular to a lithium iron phosphate battery positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] The double-sided density of the traditional thick-coated lithium iron phosphate positive electrode sheet (excluding foil) is about 140-440g / m 2 , the mass energy density is about 100-200Wh / kg. It has the characteristics of high energy density and high battery cell cost.

[0003] Thick coating of lithium iron phosphate cathode has the following advantages:

[0004] 1. Improve energy density: Increase the active material loading. Thick coating can load more positive electrode active materials on the same electrode area, thereby improving the overall energy density of the battery and enabling the battery to store more electrical energy, which is of great significance for applications such as electric vehicles that pursue high mileage; optimize space utilization. In a limited battery space, by increasing the thickness of the positive electrode coating, the space can be more fully utilized and the battery's energy storage capacity can be improved.

[0005] 2. Reduce costs: To a certain extent, thick coating can reduce the demand for other components (such as diaphragms, casings, etc.) in battery production. Because the energy of the battery is mainly provided by the positive electrode active material, increasing the load of the positive electrode active material relatively reduces the proportion of other components in the battery cost, which helps to reduce the manufacturing cost of the entire battery.

[0006] However, thick coating of lithium iron phosphate positive electrode also has certain disadvantages. Thicker positive electrode coating will increase the diffusion distance of lithium iron phosphate in the electrode, resulting in slower diffusion of lithium iron phosphate and larger internal resistance of the battery cell, thus affecting the electrochemical performance of the battery. The phenomenon is more obvious during high current charging and discharging. The internal resistance of the battery cell is large, and lithium iron phosphate cannot be embedded in and out of the positive electrode active material in time, causing the electrochemical performance of the battery cell to drop sharply.

[0007] Therefore, in recent years, the development of lithium-ion battery technology has become increasingly mature, and people no longer simply pursue the highest possible energy density, but improve the energy density of batteries while ensuring high safety. For positive electrode active materials, ternary materials have higher gram capacity and better conductivity. For example, the capacity of nickel-cobalt-manganese ternary materials is above 190mAh / g, and the working voltage is 3.6-3.7V. They are widely used in fields with high energy density requirements, but they face defects such as poor cycle performance and poor safety performance. Although lithium iron phosphate materials have lower capacity and voltage platforms and poor conductivity, their cycle performance and safety performance are excellent, and they are often used in energy storage fields and fields with high safety requirements.

[0008] In view of this, it is necessary to provide a new positive electrode plate for a lithium iron phosphate battery to overcome the problem of high resistivity of thickly coated positive electrode plates for lithium iron phosphate batteries. Summary of the invention

[0009] The main purpose of the present invention is to provide a lithium iron phosphate battery positive electrode plate and a preparation method, and a lithium ion battery to solve the above technical problems.

[0010] To achieve the above object, the present invention provides a positive electrode sheet for a lithium iron phosphate battery, comprising:

[0011] Foil layer;

[0012] A positive electrode coating applied to both sides of the foil layer, wherein the positive electrode coating comprises a first positive electrode coating close to the foil layer and a second positive electrode coating far from the foil layer;

[0013] Among them, the first positive electrode coating includes a first positive electrode active material, a first conductive agent and a first binder, and the first positive electrode active material is a lithium iron phosphate material; the second positive electrode coating includes a second positive electrode active material, a second conductive agent and a second binder, and the second positive electrode active material includes a lithium iron phosphate material and a ternary lithium material.

[0014] Furthermore, the first conductive agent includes one or more of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, and VGCF; the second conductive agent includes single-walled carbon nanotubes and other conductive agents, and the other conductive agents include one or more of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, and VGCF.

[0015] Furthermore, the first binder and the second binder both include one or more of polyvinylidene fluoride, polyacrylic acid resins, and nitrile multi-polymers.

[0016] Furthermore, in the second positive electrode active material, the mass of lithium iron phosphate accounts for 60% to 90% of the total mass of the powder of the first positive electrode active material, the first conductive agent and the first binder.

[0017] Furthermore, the first positive electrode active material, the first conductive agent and the first bonding powder account for 93-98.75%, 0.05-4% and 1.2-3% of the total mass of the three, respectively; the second positive electrode active material, the second conductive agent and the second bonding powder account for 91-98.75%, 0.05-6% and 1.2-3% of the total mass of the three, respectively.

[0018] The present invention also provides a method for preparing the above-mentioned positive electrode sheet of a lithium iron phosphate battery, comprising the steps of:

[0019] S1, stirring and mixing the first positive electrode active material, the first conductive agent and the first binder powder, and adding a solvent to obtain a first positive electrode coating slurry A;

[0020] S2, stirring and mixing the second positive electrode active material, the second conductive agent and the second binder powder, and adding a solvent to obtain a second positive electrode coating slurry B;

[0021] S3, applying slurry A to the foil layer as the current collector, drying, applying slurry B to the first positive electrode coating formed by slurry A, drying, to obtain a second positive electrode coating;

[0022] S4, die-cutting is performed to obtain the positive electrode sheet of the lithium iron phosphate battery.

[0023] Furthermore, the double-sided surface density of the positive electrode plate of the lithium iron phosphate battery is 140-440 g / m2.

[0024] Furthermore, the solvent is NMP.

[0025] The present invention also provides a lithium-ion battery, comprising the lithium iron phosphate battery positive electrode sheet as described in any one of the above items.

[0026] The present invention also provides a use of the positive electrode sheet of a lithium iron phosphate battery as described in any one of the above items as a positive electrode of a lithium ion battery.

[0027] The positive electrode plate of the lithium iron phosphate battery in the present invention includes: a foil layer; a positive electrode coating coated on the front and back sides of the foil layer, the positive electrode coating including a first positive electrode coating close to the foil layer and a second positive electrode coating away from the foil layer; wherein the first positive electrode coating includes a first positive electrode active material, a first conductive agent and a first binder, the first positive electrode active material is a lithium iron phosphate material; the second positive electrode coating includes a second positive electrode active material, a second conductive agent and a second binder, the second positive electrode active material includes a lithium iron phosphate material and a ternary lithium material. Through the double-layer coating technology, a ternary material with good conductivity is introduced as the outer layer, the conductivity of the outer layer system is improved, the resistivity of the plate is reduced, the problem of large internal resistance and poor dynamic performance of thick positive electrode coating is overcome, the chemical performance and energy density of the battery are improved, and the cost of the battery cell is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:

[0029] Figure 1 It is a schematic diagram of the process of preparing the positive electrode sheet of a lithium iron phosphate battery in the present invention.

[0030] Figure 2 It is a schematic diagram of the interlayer of the positive electrode plate of the lithium iron phosphate battery in the present invention.

[0031] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0032] The following is a clear and complete description of the technical problems solved by the embodiments of the present invention, the technical solutions adopted, and the technical effects achieved in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other equivalent or obviously modified embodiments obtained by ordinary technicians in this field without creative work fall within the scope of protection of the present invention. The embodiments of the present invention can be concretized in a variety of different ways as defined and covered in the claims.

[0033] It should be noted that in the following description, many specific details are given for ease of understanding, but it is obvious that the present invention can be implemented without these specific details.

[0034] It should be noted that, in the absence of clear limitation or conflict, the various embodiments of the present invention and the technical features therein can be combined with each other to form a technical solution.

[0035] Please combine Figure 1 and Figure 2 The present embodiment provides a positive electrode plate for a lithium iron phosphate battery, comprising:

[0036] The foil layer (current collector) is selected from one of aluminum foil, microporous aluminum foil and carbon-coated aluminum foil, with a thickness of 3 μm-20 μm, preferably carbon-coated aluminum foil 12+1+1 μm, aluminum foil 12 μm, and carbon-coated layer 1 μm;

[0037] A positive electrode coating applied to both sides of the foil layer, wherein the positive electrode coating comprises a first positive electrode coating close to the foil layer and a second positive electrode coating far from the foil layer;

[0038] Among them, the first positive electrode coating includes a first positive electrode active material, a first conductive agent and a first binder, and the first positive electrode active material is a lithium iron phosphate material; the second positive electrode coating includes a second positive electrode active material, a second conductive agent and a second binder, and the second positive electrode active material includes a lithium iron phosphate material and a ternary lithium material.

[0039] Furthermore, the first conductive agent includes one or more of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, and VGCF; the second conductive agent includes single-walled carbon nanotubes and other conductive agents, and the other conductive agents include one or more of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, and VGCF.

[0040] Single-walled carbon nanotubes have strong conductivity and are a must. When used with carbon black, they form a point-line conductive network, which improves the conductivity of the system and reduces the electrode resistance.

[0041] Furthermore, the first binder and the second binder both include one or more of polyvinylidene fluoride, polyacrylic acid resin, and nitrile multi-polymer, preferably polyvinylidene fluoride PVDF.

[0042] Furthermore, in the second positive electrode active material, the mass of lithium iron phosphate accounts for 60% to 90% of the total mass of the powder of the first positive electrode active material, the first conductive agent and the first binder.

[0043] Furthermore, the first positive electrode active material, the first conductive agent and the first bonding powder account for 93-98.75%, 0.05-4% and 1.2-3% of the total mass of the three, respectively; the second positive electrode active material, the second conductive agent and the second bonding powder account for 91-98.75%, 0.05-6% and 1.2-3% of the total mass of the three, respectively.

[0044] Specifically, the above-mentioned positive electrode sheet of the lithium iron phosphate battery is improved by the double-layer coating technology of A (inner layer / first positive electrode coating) and B (outer layer / second positive electrode coating), so as to improve the problem of high resistivity of the thickly coated positive electrode sheet. The A layer is a conventional formula, and the B layer introduces a ternary material with strong conductivity, while increasing the content of the conductive agent (single-walled carbon nanotube), improving the conductivity of the B layer system, and reducing the resistivity of the B layer sheet, thereby overcoming the problem of high resistivity of the thickly coated positive electrode sheet of the lithium iron phosphate battery.

[0045] The present invention also provides a method for preparing the above-mentioned positive electrode sheet of a lithium iron phosphate battery, comprising the steps of:

[0046] S1, stirring and mixing the first positive electrode active material, the first conductive agent and the first binder powder, and adding a solvent to obtain a first positive electrode coating slurry A; the mass of the solvent accounts for 42 to 81% of the total mass of the powder of the B layer;

[0047] S2, stirring and mixing the second positive electrode active material, the second conductive agent and the second binder powder, and adding a solvent to obtain a second positive electrode coating slurry B; the mass of the solvent accounts for 42-81% of the total mass of the powder in the B layer

[0048] S3, applying slurry A to the foil layer as the current collector, drying, applying slurry B to the first positive electrode coating formed by slurry A, drying, to obtain a second positive electrode coating;

[0049] S4, die-cutting is performed to obtain the positive electrode sheet of the lithium iron phosphate battery.

[0050] Furthermore, the double-sided surface density of the positive electrode plate of the lithium iron phosphate battery is 140-440 g / m2.

[0051] Furthermore, the solvent is NMP (N-methyl-2-pyrrolidone).

[0052] Embodiment 1:

[0053] The preparation method of the positive electrode sheet of lithium iron phosphate battery is as follows:

[0054] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0055] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0056] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0057] Cathode solvent: NMP

[0058] Positive electrode current collector: Carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0059] The method for preparing the positive electrode slurry of the lithium iron phosphate battery comprises the following steps:

[0060] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0061] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0062] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0063] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and the slurry was filtered.

[0064] The slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 400g / m 2 , drying and die-cutting to obtain the positive electrode sheet

[0065] Embodiment 2:

[0066] The preparation method of the positive electrode sheet of lithium iron phosphate battery is as follows:

[0067] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0068] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0069] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0070] Cathode solvent: NMP

[0071] Positive electrode current collector: Carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0072] The method for preparing the positive electrode slurry of the lithium iron phosphate battery comprises the following steps:

[0073] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0074] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0075] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0076] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and the slurry was filtered.

[0077] The slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 600g / m 2 , drying and die-cutting to obtain the positive electrode sheet

[0078] Embodiment 3:

[0079] The preparation method of the positive electrode sheet of lithium iron phosphate battery is as follows:

[0080] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0081] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 4%

[0082] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0083] Cathode solvent: NMP

[0084] Positive electrode current collector: Carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0085] The method for preparing the positive electrode slurry of the lithium iron phosphate battery comprises the following steps:

[0086] 100 kg of lithium iron phosphate, 4.25 kg of conductive carbon black and 2.12 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0087] 41.37 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0088] Add 29.5 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0089] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and the slurry was filtered.

[0090] The slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 600g / m 2 , drying and die-cutting to obtain the positive electrode sheet

[0091] Embodiment 4:

[0092] The preparation method of the positive electrode sheet of lithium iron phosphate battery is as follows:

[0093] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0094] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0095] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0096] Cathode solvent: NMP

[0097] Positive electrode current collector: Carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0098] The method for preparing the positive electrode slurry of the lithium iron phosphate battery comprises the following steps:

[0099] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0100] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0101] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0102] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and the slurry was filtered.

[0103] The slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 800g / m 2 , drying and die-cutting to obtain the positive electrode sheet

[0104] Embodiment 5:

[0105] The preparation method of the positive electrode sheet of lithium iron phosphate battery is as follows:

[0106] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0107] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 4%

[0108] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0109] Cathode solvent: NMP

[0110] Positive electrode current collector: Carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0111] The method for preparing the positive electrode slurry of the lithium iron phosphate battery comprises the following steps:

[0112] 100 kg of lithium iron phosphate, 4.25 kg of conductive carbon black and 2.12 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0113] 41.37 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0114] Add 29.5 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0115] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and the slurry was filtered.

[0116] The slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 800g / m 2 , drying and die-cutting to obtain the positive electrode sheet

[0117] Comparison Group 1:

[0118] Preparation method of positive electrode sheet of lithium iron phosphate battery, A layer slurry is as follows:

[0119] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0120] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0121] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0122] Cathode solvent: NMP

[0123] Positive electrode current collector: Carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0124] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0125] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0126] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0127] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry A was obtained by filtration.

[0128] The slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 200g / m 2 , drying, and then the A layer coated coil is obtained.

[0129] The B layer slurry is as follows:

[0130] Positive electrode active material 1: lithium iron phosphate / total powder mass = 70%

[0131] Positive electrode active material 2: ternary 523 / total powder mass = 25.95%

[0132] Positive electrode conductive agent 1: Conductive carbon black Super P / total powder mass = 2%

[0133] Positive electrode conductive agent 2: single-walled carbon nanotube / total powder mass=0.05%, single-walled carbon nanotube slurry solid content is 0.4%, and the solvent is NMP.

[0134] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0135] Cathode solvent: NMP

[0136] 100 kg of lithium iron phosphate, 37.07 kg of ternary 523, 2.85 kg of conductive carbon black and 2.85 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0137] 37.68 kg of NMP and 17.85 kg of single-walled carbon nanotubes were added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0138] Add 77.45 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0139] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry B was obtained by filtration.

[0140] The above-obtained B slurry is applied to the A-layer coated coil, with a double-sided surface density (excluding foil) of 200 g / m 2 , drying and die-cutting to obtain the positive electrode sheet.

[0141] Comparison Group 2:

[0142] Preparation method of positive electrode sheet of lithium iron phosphate battery, A layer slurry is as follows:

[0143] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0144] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0145] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0146] Cathode solvent: NMP

[0147] Positive electrode current collector: Carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0148] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0149] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0150] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0151] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry A was obtained by filtration.

[0152] The slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 300g / m 2 , drying, and then the A layer coated coil is obtained.

[0153] The B layer slurry is as follows:

[0154] Positive electrode active material 1: lithium iron phosphate / total powder mass = 70%

[0155] Positive electrode active material 2: ternary 523 / total powder mass = 25.95%

[0156] Positive electrode conductive agent 1: Conductive carbon black Super P / total powder mass = 2%

[0157] Positive electrode conductive agent 2: single-walled carbon nanotube / total powder mass=0.05%, single-walled carbon nanotube slurry solid content is 0.4%, and the solvent is NMP.

[0158] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0159] Cathode solvent: NMP

[0160] 100 kg of lithium iron phosphate, 37.07 kg of ternary 523, 2.85 kg of conductive carbon black and 2.85 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0161] 37.68 kg of NMP and 17.85 kg of single-walled carbon nanotubes were added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0162] Add 77.45 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0163] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry B was obtained by filtration.

[0164] The above-obtained B slurry is applied to the A-layer coated coil, with a double-sided surface density (excluding foil) of 300 g / m 2 , drying and die-cutting to obtain the positive electrode sheet.

[0165] Comparison group 3:

[0166] Preparation method of positive electrode sheet of lithium iron phosphate battery, A layer slurry is as follows:

[0167] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0168] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 4%

[0169] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0170] Cathode solvent: NMP

[0171] Positive electrode current collector: preferably carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0172] 100 kg of lithium iron phosphate, 4.25 kg of conductive carbon black and 2.12 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0173] 41.37 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0174] Add 29.5 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0175] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry A was obtained by filtration.

[0176] The A slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 300g / m 2 , drying, and then the A layer coated coil is obtained.

[0177] The B layer slurry is as follows:

[0178] Positive electrode active material 1: lithium iron phosphate / total powder mass = 70%

[0179] Positive electrode active material 2: ternary 523 / total powder mass = 25.95%

[0180] Positive electrode conductive agent 1: Conductive carbon black Super P / total powder mass = 2%

[0181] Positive electrode conductive agent 2: single-walled carbon nanotube / total powder mass=0.05%, single-walled carbon nanotube slurry solid content is 0.4%, and the solvent is NMP.

[0182] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0183] Cathode solvent: NMP

[0184] 100 kg of lithium iron phosphate, 37.07 kg of ternary 523, 2.85 kg of conductive carbon black and 2.85 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0185] 37.68 kg of NMP and 17.85 kg of single-walled carbon nanotubes were added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0186] Add 77.45 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0187] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry B was obtained by filtration.

[0188] The above-obtained B slurry is applied to the A-layer coated coil, with a double-sided surface density (excluding foil) of 300 g / m 2 , drying and die-cutting to obtain the positive electrode sheet.

[0189] Comparison group 4:

[0190] Preparation method of positive electrode sheet of lithium iron phosphate battery, A layer slurry is as follows:

[0191] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0192] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0193] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0194] Cathode solvent: NMP

[0195] Positive electrode current collector: preferably carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0196] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0197] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0198] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0199] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry A was obtained by filtration.

[0200] The A slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 400g / m 2 , drying, and then the A layer coated coil is obtained.

[0201] The B layer slurry is as follows:

[0202] Positive electrode active material 1: lithium iron phosphate / total powder mass = 70%

[0203] Positive electrode active material 2: ternary 523 / total powder mass = 25.95%

[0204] Positive electrode conductive agent 1: Conductive carbon black Super P / total powder mass = 2%

[0205] Positive electrode conductive agent 2: single-walled carbon nanotube / total powder mass=0.05%, single-walled carbon nanotube slurry solid content is 0.4%, and the solvent is NMP.

[0206] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0207] Cathode solvent: NMP

[0208] 100 kg of lithium iron phosphate, 37.07 kg of ternary 523, 2.85 kg of conductive carbon black and 2.85 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0209] 37.68 kg of NMP and 17.85 kg of single-walled carbon nanotubes were added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0210] Add 77.45 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0211] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry B was obtained by filtration.

[0212] The above-obtained B slurry is applied to the A-layer coated coil, with a double-sided surface density (excluding foil) of 400 g / m 2 , drying and die-cutting to obtain the positive electrode sheet.

[0213] Comparison group 5:

[0214] Preparation method of positive electrode sheet of lithium iron phosphate battery, A layer slurry is as follows:

[0215] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0216] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 4%

[0217] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0218] Cathode solvent: NMP

[0219] Positive electrode current collector: preferably carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0220] 100 kg of lithium iron phosphate, 4.25 kg of conductive carbon black and 2.12 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0221] 41.37 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0222] Add 29.5 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0223] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry A was obtained by filtration.

[0224] The A slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 400g / m 2 , drying, and then the A layer coated coil is obtained.

[0225] The B layer slurry is as follows:

[0226] Positive electrode active material 1: lithium iron phosphate / total powder mass = 70%

[0227] Positive electrode active material 2: ternary 523 / total powder mass = 25.95%

[0228] Positive electrode conductive agent 1: Conductive carbon black Super P / total powder mass = 2%

[0229] Positive electrode conductive agent 2: single-walled carbon nanotube / total powder mass=0.05%, single-walled carbon nanotube slurry solid content is 0.4%, and the solvent is NMP.

[0230] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0231] Cathode solvent: NMP

[0232] 100 kg of lithium iron phosphate, 37.07 kg of ternary 523, 2.85 kg of conductive carbon black and 2.85 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0233] 37.68 kg of NMP and 17.85 kg of single-walled carbon nanotubes were added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0234] Add 77.45 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0235] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry B was obtained by filtration.

[0236] The above-obtained B slurry is applied to the A-layer coated coil, with a double-sided surface density (excluding foil) of 400 g / m 2 , drying and die-cutting to obtain the positive electrode sheet.

[0237] Comparison group 6:

[0238] Preparation method of positive electrode sheet of lithium iron phosphate battery, A layer slurry is as follows:

[0239] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0240] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0241] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0242] Cathode solvent: NMP

[0243] Positive electrode current collector: preferably carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0244] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0245] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0246] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0247] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry A was obtained by filtration.

[0248] The A slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 400g / m 2 , drying, and then the A layer coated coil is obtained.

[0249] The B layer slurry is as follows:

[0250] Positive electrode active material 1: lithium iron phosphate / total powder mass = 69.9%

[0251] Positive electrode active material 2: ternary 523 / total powder mass = 25.95%

[0252] Positive electrode conductive agent 1: Conductive carbon black Super P / total powder mass = 2%

[0253] Positive electrode conductive agent 2: single-walled carbon nanotube / total powder mass = 0.15%, single-walled carbon nanotube slurry solid content is 0.4%, and the solvent is NMP.

[0254] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0255] Cathode solvent: NMP

[0256] 100 kg of lithium iron phosphate, 37.12 kg of ternary 523, 2.86 kg of conductive carbon black and 2.86 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0257] 2.01 kg NMP and 53.64 kg single-walled carbon nanotubes were added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0258] Add 39.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0259] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry B was obtained by filtration.

[0260] The above-obtained B slurry is applied to the A-layer coated coil, with a double-sided surface density (excluding foil) of 400 g / m 2 , drying and die-cutting to obtain the positive electrode sheet.

[0261] Comparison group 7:

[0262] Preparation method of positive electrode sheet of lithium iron phosphate battery, A layer slurry is as follows:

[0263] Positive electrode active material: lithium iron phosphate / total powder mass = 96%

[0264] Positive electrode conductive agent: Conductive carbon black Super P / total powder mass = 2%

[0265] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0266] Cathode solvent: NMP

[0267] Positive electrode current collector: preferably carbon-coated aluminum foil 12+1+1μm, aluminum foil 12μm, coating 1μm

[0268] 100 kg of lithium iron phosphate, 2.08 kg of conductive carbon black and 2.08 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0269] 40.5 kg of NMP was added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0270] Add 28.9 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0271] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry A was obtained by filtration.

[0272] The A slurry obtained above was coated on 12+1+1μm carbon-coated aluminum foil, with a double-sided surface density (excluding foil) of 400g / m 2 , drying, and then the A layer coated coil is obtained.

[0273] The B layer slurry is as follows:

[0274] Positive electrode active material 1: lithium iron phosphate / total powder mass = 90%

[0275] Positive electrode active material 2: ternary 523 / total powder mass = 5.85%

[0276] Positive electrode conductive agent 1: Conductive carbon black Super P / total powder mass = 2%

[0277] Positive electrode conductive agent 2: single-walled carbon nanotube / total powder mass = 0.15%, single-walled carbon nanotube slurry solid content is 0.4%, and the solvent is NMP.

[0278] Positive electrode binder: polyvinylidene fluoride PVDF / total powder mass = 2%

[0279] Cathode solvent: NMP

[0280] 100 kg of lithium iron phosphate, 6.5 kg of ternary 523, 2.22 kg of conductive carbon black and 2.22 kg of polyvinylidene fluoride were added to a stirring tank, and stirred at a revolution rate of 10 r / min and a rotation rate of 400 r / min for 20 min.

[0281] 1.56 kg NMP and 41.66 kg single-walled carbon nanotubes were added, and the mixture was stirred at a revolution rate of 15 r / min and a rotation rate of 400 r / min for 80 min.

[0282] Add 31.0 kg NMP and stir at a revolution rate of 18 r / min and a rotation rate of 1000 r / min for 1.5 h.

[0283] The mixture was stirred at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and slurry B was obtained by filtration.

[0284] The above-obtained B slurry is applied to the A-layer coated coil, with a double-sided surface density (excluding foil) of 400 g / m 2 , drying and die-cutting to obtain the positive electrode sheet.

[0285] Table 4. Electrode sheet resistivity test of the embodiment and comparison group

[0286]

[0287] It can be concluded from the above table that the positive electrode plate of the lithium iron phosphate battery of the present invention uses double-layer coating technology to introduce ternary materials with good conductivity and single-walled carbon nanotubes with strong conductivity into the B layer, thereby improving the conductivity of the B layer system and reducing the resistivity of the plate. For Example 1-5, the greater the density of the positive electrode coating surface, the greater the resistivity of the plate, and increasing the content of the conductive agent does not improve significantly. For Comparative Group 1-7, the greater the density of the positive electrode coating surface, the greater the resistivity of the plate, and the ternary materials with good conductivity and single-walled carbon nanotubes with strong conductivity are introduced into the B layer to improve the conductivity of the B layer system and reduce the resistivity of the plate, and the improvement is obvious.

[0288] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.

Claims

1. A positive electrode plate for a lithium iron phosphate battery, characterized in that: include: Foil layer; A positive electrode coating applied to both sides of the foil layer, wherein the positive electrode coating comprises a first positive electrode coating close to the foil layer and a second positive electrode coating far from the foil layer; Among them, the first positive electrode coating includes a first positive electrode active material, a first conductive agent and a first binder, and the first positive electrode active material is a lithium iron phosphate material; the second positive electrode coating includes a second positive electrode active material, a second conductive agent and a second binder, and the second positive electrode active material includes a lithium iron phosphate material and a ternary lithium material.

2. The positive electrode plate of a lithium iron phosphate battery according to claim 1, characterized in that: The first conductive agent includes one or more of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, and VGCF; the second conductive agent includes single-walled carbon nanotubes and other conductive agents, and the other conductive agents include one or more of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, and VGCF.

3. The positive electrode plate of a lithium iron phosphate battery according to claim 1, characterized in that: The first binder and the second binder both include one or more of polyvinylidene fluoride, polyacrylic acid resin, and nitrile multi-polymer.

4. The positive electrode plate of a lithium iron phosphate battery according to claim 1, characterized in that: In the second positive electrode active material, the mass of lithium iron phosphate accounts for 60% to 90% of the total mass of the powder of the first positive electrode active material, the first conductive agent and the first binder.

5. The positive electrode plate of a lithium iron phosphate battery according to claim 1, characterized in that: The first positive electrode active material, the first conductive agent and the first bonding powder account for 93-98.75%, 0.05-4% and 1.2-3% of the total mass of the three, respectively; the second positive electrode active material, the second conductive agent and the second bonding powder account for 91-98.75%, 0.05-6% and 1.2-3% of the total mass of the three, respectively.

6. A method for preparing a positive electrode sheet of a lithium iron phosphate battery as claimed in claims 1-5, characterized in that: Includes steps: S1, stirring and mixing the first positive electrode active material, the first conductive agent and the first binder powder, and adding a solvent to obtain a first positive electrode coating slurry A; S2, stirring and mixing the second positive electrode active material, the second conductive agent and the second binder powder, and adding a solvent to obtain a second positive electrode coating slurry B; S3, applying slurry A to the foil layer as the current collector, drying, applying slurry B to the first positive electrode coating formed by slurry A, drying, to obtain a second positive electrode coating; S4, die-cutting is performed to obtain the positive electrode sheet of the lithium iron phosphate battery.

7. The method for preparing a positive electrode sheet for a lithium iron phosphate battery according to claim 6, characterized in that: The double-sided surface density of the positive electrode sheet of the lithium iron phosphate battery is 140-440g / m 2 .

8. The method for preparing a positive electrode sheet for a lithium iron phosphate battery according to claim 6, characterized in that: The solvent is NMP.

9. A lithium ion battery, characterized in that: It comprises a positive electrode plate for a lithium iron phosphate battery as described in any one of claims 1 to 5.

10. Use of the positive electrode sheet of a lithium iron phosphate battery as claimed in any one of claims 1 to 5 as a positive electrode of a lithium ion battery.

Citation Information

Cited By

  • Positive pole piece, lithium ion battery comprising positive pole piece, and electronic device comprising positive pole piece

    CN122067976A

  • A positive electrode sheet, and a lithium ion battery and an electronic device comprising the same

    CN122067976B